2020
DOI: 10.3233/jad-200070
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs Based Molecular Links in Type 2 Diabetes, Ischemic Stroke, and Vascular Dementia

Abstract: This article reviews recent advances in the study of microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and their functions in type 2 diabetes mellitus (T2DM), ischemic stroke (IS), and vascular dementia (VaD). miRNAs and lncRNAs are gene regulation markers that both regulate translational aspects of a wide range of proteins and biological processes in healthy and disease states. Recent studies from our laboratory and others have revealed that miRNAs and lncRNAs expressed differently are potential therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 208 publications
0
23
0
Order By: Relevance
“…First, several risk factors could influence the expression of peripheral ncRNAs, consequently confounding the accuracy of the biomarker ncRNAs. Previous research have indicated that almost all risk factors could potentially result in different expression of certain miRNAs in peripheral blood, including age, 81 obesity, 82 type 2 diabetes, 83,84 and coronary artery diseases 85 . Here, in this study, though we matched one of the most fundamental confounders, age, the impact of some other comorbidities was hard to control because of the complicated healthy condition background of each patients, especially those with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…First, several risk factors could influence the expression of peripheral ncRNAs, consequently confounding the accuracy of the biomarker ncRNAs. Previous research have indicated that almost all risk factors could potentially result in different expression of certain miRNAs in peripheral blood, including age, 81 obesity, 82 type 2 diabetes, 83,84 and coronary artery diseases 85 . Here, in this study, though we matched one of the most fundamental confounders, age, the impact of some other comorbidities was hard to control because of the complicated healthy condition background of each patients, especially those with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…IS is a severe neurological disease with serious impairment of the neurological function. 38 Growing literature has shown that down-regulation of lncRNAs is implicated in the pathological process of IS, such as lncRNA Oprm1, 39 lncRNA ZFAS1 40 and lncRNA ANRIL. 34 Coincident with expression trend of previous studies, we also observed that SNHG7 was down-regulated by MCAO treatment in brain tissues of mice and by OGD/R treatment in PC12 cells, implying that SNHG7 might involve in the pathologies of IS.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs perform multiple important functions in the cell, including cell growth, cell proliferation, embryonic development, tissue differentiation, and apoptosis [ 10 ]. MicroRNAs have also been found to improve the gene-regulatory processes in cerebrovascular disease.…”
Section: Micrornasmentioning
confidence: 99%
“…MicroRNA-mediated gene silencing controls a diverse set of important cellular processes, such as cellular senescence and neurodegeneration. Extensive research has also revealed that microRNAs are implicated in a number of human diseases, including cancer, diabetes, obesity, stroke, Alzheimer’s, Parkinson’s, and Huntington’s, as well as aging [ 8 , 10 , 11 , 12 , 13 ]. These circulatory microRNAs can be used as biomarkers for human diseases [ 8 , 10 , 11 , 12 , 13 ].…”
Section: Micrornasmentioning
confidence: 99%